2016
DOI: 10.4137/ccrpm.s40939
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide and High-Sensitive Troponin T Concentrations Correlate with Effectiveness of Short-Term CPAP in Patients with Obstructive Sleep Apnea and Coronary Artery Disease

Abstract: The risk of cardiovascular complications is increased in patients with obstructive sleep apnea (OSA). Continuous positive airway pressure (CPAP) is the most effective way to treat clinically significant OSA. We hypothesized that the concentrations of the cardiac risk markers N-terminal brain natriuretic peptide (NT-proBNP) and high-sensitive troponin T (hs-TropT) correlate with the effectiveness of CPAP therapy in patients with OSA and coexisting coronary artery disease (CAD). Twenty-one patients with severe O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Previous studies have not found a correlation between AHI and the level of NT-proBNP after adjusting for potential confounding factors, while Ljunggren et al reported a dose–response relationship between the severity of OSA and NT-proBNP levels in female patients [ 44 , 45 , 46 ]. Moreover, several other studies reported that the severity of OSAS was not independently associated with the level of hs-TropT, although the hs-TropT level was correlated with AHI in patients with severe OSAS and coexisting coronary artery disease [ 47 , 48 ]. Therefore, future studies are needed to investigate the feasibility of these two cardiac biomarkers as predictors of cardiovascular risk in patients with suspected OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not found a correlation between AHI and the level of NT-proBNP after adjusting for potential confounding factors, while Ljunggren et al reported a dose–response relationship between the severity of OSA and NT-proBNP levels in female patients [ 44 , 45 , 46 ]. Moreover, several other studies reported that the severity of OSAS was not independently associated with the level of hs-TropT, although the hs-TropT level was correlated with AHI in patients with severe OSAS and coexisting coronary artery disease [ 47 , 48 ]. Therefore, future studies are needed to investigate the feasibility of these two cardiac biomarkers as predictors of cardiovascular risk in patients with suspected OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Tasci et al [ 48 ] reported that nasal CPAP treatment significantly reduced NT-proBNP in patients with normotensive and hypertensive OSAS. Similarly, Strehmel et al reported reduced NT-proBNP levels after CPAP treatment in patients with OSAS and coronary artery disease [ 49 ]. In the present study, we have found that 6 months CPAP treatment for OSAS significantly reduced the NT-proBNP levels which means reduced ventricular wall stress.…”
Section: Discussionmentioning
confidence: 99%
“…One study separated participants into two groups based on whether coexisting CAD. 12 ASV therapy was adopted in two studies. 15 , 16 The characteristics of the 11 included studies were summarized in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%